Analysis of Customer Satisfaction in PT. X Using Service Quality Method and Importance-Performance Analysis - Rai N. Kodrat; Burhan Primanintyo (President University, 2017)
PT. X is a service company that focus on logistic and transportation. Fleet department is the department that responsible to handle, arrange, and monitor the delivery service in PT. X. It means that Fleet department is also responsible if there is any customer complaint. Increasing number in customer complaint means that the customer is not satisfy with the delivery service provided by the company. This research is conducted in order to determine what are the factors that influence customer satisfaction. By using Service Quality method, Gap Analysis, and Importance-Performance Analysis, the result will be in a form of conclusion and recommendation. The result for improvements are driver and truck safety appearance, easiness of contacting the company when there is a complaint, and information regarding with the delivery service. After determining the factors that most influencing customer satisfaction, Service Blueprint and Check List is made inorder to improve and control the factors occurred.